On the stability of the third order partial differential equation with time delay - Ashyralyev, A.; Ibrahim, S.; Hincal, E. (Karagandy University of the name of acad. E.A. Buketov, 2025)
In this paper, the initial value problem for a third-order partial differential equation with time delay within a Hilbert space was analyzed.We establish a key theorem regarding the stability of this problem. Additionally, we demonstrate how this stability theorem can be applied to the third-order partial differential equation with time delay.
Keywords: 58D25; 35L90; 35G10; 2020 Mathematics Subject Classification; time delay; third order partial differential equations; stability